Nature+ Quantitative Monitoring Household Survey, Colombia - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The NATURE+ survey conducted in Colombia integrated household and community-level questionnaires to develop a comprehensive understanding of the socio-economic, agricultural, and environmental dynamics influencing potential beneficiaries of NATURE+ interventions. The study focused on two key departments: Nariño and Putumayo. At the household level, the survey collected detailed socio-economic and demographic data, including household composition, education levels, land ownership, income sources, self-employment activities, and asset ownership. This information provides crucial insights into the economic conditions of the surveyed population. The survey also documented agricultural practices on farms and in chagras—traditional agroforestry systems maintained by Indigenous communities. Specific attention was given to crop and livestock production, crop biodiversity, and the use of fertilizers and pesticides. The survey further investigated the adoption of nature-positive solutions, including agroforestry practices, environmental management (such as waste handling and renewable energy use), and awareness of biodiversity benefits. Issues related to food security and dietary diversity were also addressed. At the community level, the questionnaire aimed to capture broader socio-economic, environmental, and institutional factors across selected communities in Cumbal (Nariño) and multiple municipalities in Putumayo. It gathered demographic estimates—such as population size, gender and age composition, and number of households—to construct a socio-economic profile of each community. The survey assessed the prevalence and benefits of nature-positive practices, such as biodiversity conservation, agroforestry, and sustainable land management. It also evaluated the role of external actors, including NGOs and extension agencies, in promoting these practices. Additional components covered community infrastructure, natural resource governance, and ongoing sustainability initiatives.